Effect of gold nanoparticles on Sm3+ luminescence in tellurite glasses. (2018) - Ruangtaweep, Y.; Yasaka, P.; Kaewkhao, J.
Abstract: The effects of gold nanoparticles (AuNPs) on luminescence properties of tellurite glasses containing samarium ions (Sm 3+ ) have been investigated. The glass samples with chemical composition of (53.5-x(TeO2 : 10ZnO: 35BaO: 1.5Sm2 O3 : xAuNPs (where x= 0.00, 0.01, 0.02, 0.03, 0.04, and 0.05% by mol) were prepare by the conventional melt quenching technique at 950 °C in ambient atmosphere. The results show that the density and molar volume of glass not depend on AuNPs concentration. The NIR absorption spectra in range 850-2, 200 nm are observed eight bands at 948, 1083, 1237, 1385, 1489, 1541, 1592 and 1970 nm. The luminescence spectra of the Sm 3+ doped in glasses are observed at 564 ( 4 G5/2 6 H5/2 ), 600 ( 4 G5/2 6 H7/2 ), 646 ( 4 G5/2 6 H9/2 ) and 707 ( 4 G5/2 6 H11/2 ) nm when excited by a 405 nm source. Moreover, the luminescence intensity of all the emission bands is increased with increasing of AuNPs concentration.